2014
DOI: 10.1097/aln.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 2A Localized in the Spinal Cord Contributes to Inflammatory Pain Processing

Abstract: Our findings indicate that PDE2A contributes to the processing of inflammatory pain in the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Knockout studies of PDE11A have implicated this gene in regulating social behaviors and anxiety 43 . In the dorsal horn, cyclic nucleotide signaling contributes to pain-related neuronal plasticity, and other members of the phosphodiesterase family have been directly implicated in the pathogenesis of inflammatory and neuropathic pain 44 . Accordingly, we selected Pde11a for further examination.…”
Section: Resultsmentioning
confidence: 99%
“…Knockout studies of PDE11A have implicated this gene in regulating social behaviors and anxiety 43 . In the dorsal horn, cyclic nucleotide signaling contributes to pain-related neuronal plasticity, and other members of the phosphodiesterase family have been directly implicated in the pathogenesis of inflammatory and neuropathic pain 44 . Accordingly, we selected Pde11a for further examination.…”
Section: Resultsmentioning
confidence: 99%
“…Knockout studies of PDE11A have implicated this gene in regulating social behaviors and anxiety (Hegde et al, 2016a;2016b). In the dorsal horn, cyclic nucleotide signaling contributes to pain-related neuronal plasticity, and other members of the phosphodiesterase family have been directly implicated in the pathogenesis of inflammatory and neuropathic pain (Kallenborn-Gerhardt et al, 2014). Previous studies have detected Pde11a transcript and PDE11A protein in the bulk analyses of the spinal cord, but its cellular expression pattern is unknown (Kelly, 2015).…”
Section: Enzymesmentioning
confidence: 99%
“…There is general consensus that PDE2A is abundant in the central nervous system of mammals, especially in the laminae I and II of spinal dorsal horn in rats [20, 34]. In addition, PDE2A might contribute to acute inflammatory pain processing [19]. Recent experiments have detected that an inhibitor of PDE2A had anti-inflammatory and analgesic effects [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that inhibitors of PDEs inhibit the release of proinflammatory cytokines by cAMP/cGMP signaling pathways in depression, pulmonary hypertension, erectile dysfunction, and sepsis [17, 18]. Wiebke and Ruirui et al found transient PDE2A mRNA upregulation after hind paw inflammation that was accompanied by enhanced acute mechanical paw withdrawal latencies, which indicated that PDE2A likely contributed to acute radicular inflammation and pain [19]. PDE2A can hydrolyze both cAMP and cGMP and preferentially hydrolyzes cAMP after activation by cGMP [20].…”
Section: Introductionmentioning
confidence: 99%